Siblings, Friends, and Mates : Development of a Word-Pair Association Task to Measure Implicit Sexual Response to Different Relationship Partners - Werner, Amanda; Fritsch, Amber; Johnson, Jennifer L. (My University, 2012)
This study looked at theories of sexual attraction of men and women. Starting with a scenario of various relationships--opposite-sex sibling, romantic partner, or an opposite-sex friend--the sexual response of a word-pair association task was observed.
Color poster with text and graphs.
Keywords: Man-woman relationships; Language and languages--Sex differences; Thought and thinking--Sex differences; Posters